Transformasi Menuju Keberlanjutan: UMKM Indonesia dalam Menghadapi Tantangan Digital - Bahtiar, Habib; Rabbany, Lalu Rizal; Bele, Yasinta Falentina; Husna, Munadia; Matulessy, Gracia Selvi (Jurnal Ekonomi dan Bisnis, 2025)
Digital transformation is a key element for MSMEs in Indonesia in increasing productivity, competitiveness, and sustainability. Although important, MSMEs face various obstacles in adopting digital technology, such as limited access, low digital literacy, and lack of technological skills. This study aims to investigate the factors that affect the success of digital transformation in MSMEs and identify strategies that support technology integration in their operations. Using the Systematic Literature Review (SLR) design, this study evaluates literature related to the digital transformation of MSMEs in Indonesia through the PICOS (Population, Intervention, Comparison, Outcome, Study design) framework to formulate the right research question (RQ). The results of the study show that the biggest challenges for MSMEs include limited access to technology and low digital literacy. Recommended strategies include increasing digital literacy, developing technological skills, and innovating business models. The implications of this study show the need for investment in digital skills training, the formation of supporting policies, collaboration with the private sector, and strengthening infrastructure from the government to ensure the sustainability and success of MSMEs in the digital era.